The Drama of Humanitarian Intervention : Unreliable Narration in an Age of (Ab)use of Human Rights - Natalie Joy Marrer
This paper looks at the contentious debate surrounding humanitarian intervention through a critical, narratological lens. By questioning the roles cast and identities constituted, in what could be compared to a theatrical drama, focus is given to the unreliable narration of the most powerful characters on the international stage - from the US to the UN - and its impact on the political and legal stances taken in various contexts. On a meta-level, it examines the conditions that enable this unreliable narration, by pointing out a problematic flexibility owing to the paradoxes and conflation entrenched in human rights rhetoric; what some call a budding 'humanity's law'. Attention is meant to be drawn to the power of mental imagery conjured up by intervention narratives, based on the story of saving innocents, as embodiments of humanity. The goal is to foster self-reflection among readers working in humanitarian intervention, within the epistemic community of international lawyers, and beyond. We extend our heartfelt thanks to the Vahabzadeh Foundation for financially supporting the publication of best works by young researchers of the Graduate Institute, giving a priority to those who have been awarded academic prizes for their master's dissertations.